A river without tributaries - Liberating the mind through harnessing grassroots creativity - Sherry Chand, P.G. Vijaya; Gupta, Anil K. (1996)
The authors, in an apparent bid to emphasise the critical need for assimilation of the logic and spirit behind the drive of liberalisation by the common man in the street in the midst of realities that mark our present social ethos, raise questions on validity of claims of benefit accruing therefrom, highlight - through the metaphor of river and its strength-providing tributaries - the importance of fuller play of mass creativity in attaining the visualised goals of liberalisation. - Reproduced
Keywords: Liberalization - India; Economic liberalization